ESTIMATION OF AGE FROM PELVIS – A RADIOLOGICAL STUDY (Indian Internet Journal of Forensic Medicine and Toxicology, 2004)
Estimation of age is an important task for forensic experts especially in developing countries where birth records are often not well maintained. Appearance and fusion of different ossification centres with their corresponding bones has been proved to be a very good and reliable tool for this purpose.  In the present study a careful observation was done, for the age related fusion of iIium, ischium and pubis in hip bone by calcification of triradiate cartilage and appearance of centers of Iliac crest and ischial tuberosity and their fusion with corresponding bones in 202 individuals of both the sexes by X-ray examination of pelvis.
Keywords: observation; Forensic experts